2022
DOI: 10.1111/mec.16380
|View full text |Cite
|
Sign up to set email alerts
|

Wild sunflower goes viral: Citizen science and comparative genomics allow tracking the origin and establishment of invasive sunflower in the Levant

Abstract: Globalization and intensified volume of trade and transport around the world are accelerating the rate of biological invasions. It is therefore increasingly important to understand the processes through which invasive species colonize new habitats, often to the detriment of native flora. The initial steps of an invasion are particularly critical, as the introduced species relies on limited genetic diversity to adapt to a new environment. However, our understanding of this critical stage of the invasion is curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, we were able to accurately determine and monitor the molecular epidemiology of circulating lagoviruses in Australia. Altogether, consistent with numerous studies in the literature involving citizen science [32][33][34][35][36], the implementation of the rabbit and lagovirus surveillance program has demonstrated that it is a valuable resource to reliably obtain robust data to determine and monitor the genomic epidemiology and diversity of lagoviruses. It is therefore critical to sustain such programs for the long term to monitor the emergence of new RHDV incursions and/or recombinant variants which may affect wild and domestic rabbit populations.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Furthermore, we were able to accurately determine and monitor the molecular epidemiology of circulating lagoviruses in Australia. Altogether, consistent with numerous studies in the literature involving citizen science [32][33][34][35][36], the implementation of the rabbit and lagovirus surveillance program has demonstrated that it is a valuable resource to reliably obtain robust data to determine and monitor the genomic epidemiology and diversity of lagoviruses. It is therefore critical to sustain such programs for the long term to monitor the emergence of new RHDV incursions and/or recombinant variants which may affect wild and domestic rabbit populations.…”
Section: Discussionmentioning
confidence: 59%
“…Citizen science is now regularly employed in multiple disciplines, such as biological conservation [31], invasive species management [32][33][34][35][36], and education [37], substantially impacting data collection. It has enabled researchers to obtain large datasets with sample numbers ranging from the tens to the millions, depending on the scale of the population and geography by which the citizen science program is implemented.…”
Section: Introductionmentioning
confidence: 99%
“…annuus ) in eastern North America 155 and currently grows worldwide as an oilseed crop 156 . Wild sunflower is native to North America and has been introduced in many areas, including southern 111 and eastern Europe, 157 Australia, 158 Israel, 159 and central Argentina 160 . In the introduced areas, it typically grows as a ruderal species on roadsides, field margins, and ditches, although weedy populations have also been reported 51,111,157 .…”
Section: Case Studiesmentioning
confidence: 99%
“…Therefore, if just one propagule is needed to establish a population, variation in propagule pressure might linearly predict, albeit with substantial uncertainty, the probability of a successful colonization event. However, establishment from one propagule involves a severe founder effect, while genetic diversity may be correlated with successful establishment [13]. High propagule pressure generated by propagules arriving from multiple parts of a species range, in contrast, would promote genetic diversity and enhance establishment.…”
Section: Determinants Of Post-ldd Establishment Success (1) Propagule...mentioning
confidence: 99%